A Case of Tandem Plug Embolization for an Aberrant Right Subclavian Artery during Debranching Thoracic Endovascular Aortic Repair - Onzuka, Tatsushi (Ann Vasc Dis, 2016)
Aberrant right subclavian artery embolization is problematic in debranching thoracic endovascular aortic repair, because concomitant bypass grafting to the right upper arm may hinder complete embolization. We report a case of a thoracic aortic aneurysm with aberrant right subclavian artery successfully treated with debranching thoracic endovascular aortic repair and bypass grafting. Although endoleakage was found from aberrant right subclavian artery after single use of Amplatzer vascular plug, additional deployment of Amplatzer vascular plug II completely eliminated residual endoleakage. This simple technique is useful for the aberrant right subclavian artery embolization in debranching thoracic endovascular aortic repair.